Outcomes of retropupillary iris-claw lens implantation - Panchbhai, Diksha; Rao, A. Tarakeswara; Satyavathi, G.; Viswabharathi, P.; Manjula, P. (International Journal of Research in Medical Sciences, 2023)
Background: Inadequate posterior capsular support during cataract surgery makes it difficult to implant posterior chamber intraocular lens.One of the secondary intraocular lens implantation options is iris claw lens.Retropupillary iris claw lens is preferred than anterior because chances of damage to the anterior chamber angle and iris root are avoided as the lens is fixed to the mid periphery of iris. The prospective study aims to analyse the visual outcomes and immediate postoperative complications after retropupillary iris-claw lens implantation in a tertiary care hospital. Methods: It was a prospective study done conducted on 24 patients with inadequate posterior capsular support in which retropupillary iris-claw lens implantation was done from December 1, 2021 to May 31, 2022 at Government Regional Eye Hospital, Visakhapatnam. Immediate postoperative complications were noted. Final visual outcomes were noted after 2 months. Results: The study comprised of 24 eyes. The mean patient age was 55.91 years (range 44-77 years).The IOLs were inserted during primary lens surgery in 16 eyes (66.6%) and as a secondary procedure in 8 aphakic eyes (33.4%). The mean postoperative intraocular pressure was 15.1 mmHg. Majority of the eyes had best corrected visual acuity of 6/12 (41.6%).The most common immediate postoperative complication was pupil ovalization (25%) and striate keratopathy (25%). Least common complication was choroidal detachment (3.6%). Conclusions: Visual outcomes of primary and secondary iris claw implantation were similar. The retro-pupillary iris-claw lens implantation provided good visual outcome with tolerable complications. It can be used in eyes with inadequate posterior capsular support.